Ññoṅʻ ramʻʺ khetʻ nhacʻ 40 rāja vaṅʻ, 1073 mha 1113 - Lakʻvai Noʻrathā, 1723 or 4-1791 or 2. (Mranʻ mā mhu bimānʻ cā pe bhaṇʻ, 1980)
Brief history of Burma, 1711-1751; reproduced of an 18th century manuscript.